Lebrikizumab monotherapy impacts on quality of life scores through improved itch and sleep interference in two Phase 3 trials - Jennifer Soung; Sonja Ständer; Jan Gutermuth; Ignasi Pau-Charles; Zach Dawson; Fan Emily Yang; Luna Sun; Evangeline Pierce; Hany Elmaraghy; Linda Stein-Gold (Taylor & Francis Group, 2024)
AbstractBackground Lebrikizumab improved itch, interference of itch on sleep, and quality of life (QoL) in patients with moderate-to-severe atopic dermatitis (AD), in two Phase 3 trials at 16 weeks compared to placebo.Objectives We assess improvements in itch and sleep interference due to itch and their impact on QoL measurements after treatment.Methods Data were analyzed from ADvocate1 (NCT04146363) and ADvocate2 (NCT04178967) in patients with moderate-to-severe AD. QoL was evaluated using Dermatology Life Quality Index (DLQI) at Week 16 in patients (>16 years of age) who were itch responders/non-responders (defined as ≥4-point improvement in Pruritus Numeric Rating Scale) or Sleep-Loss Scale responders/non-responders (defined as ≥2-point improvement in itch interference on sleep).Results In ADvocate1 and ADvocate2, significantly greater proportions of itch responders had a clinically meaningful improvement in measures related to QoL (DLQI scores (0/1), ≤5 DLQI total score and ≥4-point DLQI improvement) compared to itch non-responders. In both studies, a significantly greater proportion of Sleep-Loss Scale responders, reported a DLQI score of (0/1), DLQI total score of ≤5 and DLQI improvement of ≥4 points compared to Sleep-Loss Scale non-responders.Conclusions Improvement in itch and sleep interference due to itch is associated with improvement in the QoL of patients after treatment with lebrikizumab for moderate-to-severe AD.ClinicalTrials.gov registration NCT04146363 (ADvocate1) and NCT04178967 (ADvocate2).